Work–Life Balance in the Automotive Industry: The Effects of Job Stress, Job Satisfaction, and Organizational Commitment - Egi Andiyana; Dessy Putri Mutiarani; Andrean Eko Haryoko; Ischak P Lumbantobing (Manunggal Halim Jaya, 2026)
This research investigates the determinants of work–life balance by emphasizing the role of quality of work life, with job stress, job satisfaction, and organizational commitment serving as mediating variables within the automotive industry in Tangerang Regency, Indonesia. A quantitative approach was adopted through a survey design involving 180 employees employed in the automotive sector. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the interrelationships among the constructs and to assess the proposed structural framework. The results demonstrate that quality of work life plays a pivotal role in alleviating job stress while concurrently improving employees’ levels of job satisfaction and organizational commitment. In addition, job stress, job satisfaction, and organizational commitment were found to significantly influence employees’ work–life balance. These findings indicate that work–life balance is shaped not only by organizational conditions but also by employees’ psychological states and work-related attitudes arising from their perceptions of the work environment. From a theoretical standpoint, this study advances the literature by offering deeper insight into the processes through which quality of work life influences work–life balance via psychological and affective mechanisms. Practically, the results provide important guidance for managers in the automotive industry in developing policies that enhance quality of work life, thereby promoting employee well-being and supporting long-term organizational sustainability.